The complications of cyclosporine a in pediatric use and its effectiveness in treating pediatric congenital heart diseases-a meta analysis in combined with a retrospective clinical study - Xue, Yiting; She, Siqi; Sun, Sijuan; Chen, Junxian; Ye, Lincai; Huang, Yanhui (Frontiers in Pharmacology, 2025)
BackgroundAdvances in surgical techniques have significantly enhanced perioperative survival rates in children with congenital heart diseases (CHDs). However, a growing population of adolescent and adult CHD survivors now face long-term challenges, including increased susceptibility to arrhythmia and impaired exercise tolerance. Preclinical studies suggested that these issues may stem from deficits in lung and cardiomyocyte maturation, driven by neonatal immune activation. The immunosuppressant cyclosporine A (CsA) has shown potential in correcting these maturational deficits in animal models. Nevertheless, the pediatric safety profile of CsA and its therapeutic efficacy for CHDs in clinical setting remain poorly characterized.MethodsWe first conducted a meta-analysis to evaluate complication rates associated with CsA treatment in pediatric populations. We then performed a large, single center retrospective study of 2,439 children treated with CsA to evaluate: (1) the incidence of complications, (2)relevant laboratory parameters, and (3) its therapeutic efficacy in CHD cases.ResultsOur meta-analysis identified infection (55.76%), hirsutism (28.34%), and upper respiratory tract infection (20.22%) as the three most frequent complications observed in CsA-treated pediatric patients. In our clinical cohort (98.97% Han ethnicity; 72.24% from East China), aplastic anemia was the primary indication for CsA treatment (44.73%). Consistent with the meta-analysis, infection remained the predominant complication (overall incidence:17.02%; accounting for 55.78% of all complicated cases). The most commonly detected pathogens were cytomegalovirus (CMV, 7.95%), Epstein-Barr virus (EBV, 5.78%), and herpesvirus (3.6%). Furthermore, following CsA administration, we observed significant elevations in two key infection biomarkers C-reactive protein (CRP) and procalcitonin (PCT). Among these 2,439 patients, CsA was primarily used for immunosuppression in bone marrow transplantation for leukemia, and autoimmune diseases. Sixteen of these patients had CHDs. In this CHD subgroup, CsA treatment was associated with significant improvements in left ventricular ejection fraction (LVEF) and fractional shortening (LVFS) (both p < 0.05).ConclusionTo our knowledge, this is the largest pediatric study on CsA to date. It demonstrates that immunosuppressants like CsA are rarely used specifically to treat children with isolated CHDs. During CsA therapy in children, infection may emerge as the most critical complication requiring vigilant monitoring. Notably, our findings provide preliminary clinical evidence supporting the potential of immunosuppressive therapy to ameliorate CHD-associated cardiomyocyte maturation deficits.Clinical Trial Registrationhttps://www.chictr.org.cn/, identifier ChiCTR2500103672.